2022
DOI: 10.3390/antiox11010142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of N-Arachidonoyl Dopamine and N-Docosahexaenoyl Dopamine on the Expression of Neurotrophic Factors in Neuronal Differentiated Cultures of Human Induced Pluripotent Stem Cells under Conditions of Oxidative Stress

Abstract: Oxidative stress (OS) is implicated in the pathogenesis of several neurodegenerative diseases. We have previously shown that N-acyl dopamines (N-ADA and N-DDA) protect the neural cells of healthy donors and patients with Parkinson’s disease from OS. In this study, we assessed the effects of N-acyl dopamines on the expression of neurotrophic factors in human-induced pluripotent stem cell-derived neuronal cultures enriched with dopaminergic neurons under conditions of OS induced by hydrogen peroxide. We showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…However, the accumulation of excessive ROS can occur in cells under certain stimuli, which can lead to a redox imbalance and oxidative stress. This can cause damage to DNA, in ammation, protein denaturation, and lipid peroxidation [31,32]. The results showed that the treatment of TM4 cells with TiO 2 NPs resulted in signi cantly elevated ROS levels when compated to that of the control group cells, suggesting that TiO 2…”
Section: Dicussionmentioning
confidence: 99%
“…However, the accumulation of excessive ROS can occur in cells under certain stimuli, which can lead to a redox imbalance and oxidative stress. This can cause damage to DNA, in ammation, protein denaturation, and lipid peroxidation [31,32]. The results showed that the treatment of TM4 cells with TiO 2 NPs resulted in signi cantly elevated ROS levels when compated to that of the control group cells, suggesting that TiO 2…”
Section: Dicussionmentioning
confidence: 99%